2010
DOI: 10.2174/1876396001003010063
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and In Vitro-Transcription of Chymosin Gene in E. coli~!2009-12-11~!2010-01-07~!2010-02-02~!

Abstract: Chymosin, commonly known as rennin, is the main milk-coagulating enzyme available in rennet. RNA was extracted from the abomasum of a suckling calf water buffalo and was subjected to RT-PCR using degenerate primers to amplify 850bp of the chymosin gene. The sequence was aligned with 19 different mammals' chymosin genes. The sequence revealed that there is a similarity to them ranging from 64% to 98%. The purified recombinant proteins were obtained from the transformed E. coli and yeast. The clotting activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Recombinant pro-chymosin is expressed in bacteria in insoluble form and it is presented in the inclusion bodies. This finding has been reported for the production of recombinant bovine chymosin in E. coli (Mule et al, 2009;El-Sohaimy et al, 2010 andMenzella, 2011). The recombinant camel chymosin behaves like the bovine one that is presented in inclusion bodies and is not presented in the cell free extract (Fig.…”
Section: Solubilization and Renaturation Of Recombinant Prochymosinsupporting
confidence: 80%
See 4 more Smart Citations
“…Recombinant pro-chymosin is expressed in bacteria in insoluble form and it is presented in the inclusion bodies. This finding has been reported for the production of recombinant bovine chymosin in E. coli (Mule et al, 2009;El-Sohaimy et al, 2010 andMenzella, 2011). The recombinant camel chymosin behaves like the bovine one that is presented in inclusion bodies and is not presented in the cell free extract (Fig.…”
Section: Solubilization and Renaturation Of Recombinant Prochymosinsupporting
confidence: 80%
“…Therefore, it could be concluded that biologically active chymosin expressed in fungi (Kappeler, 2006) or yeast (Wang et al, 2015) can be produced in E. coli after solubilization, renaturation, and acidic activation. Although, calf chymosin has been expressed in E. coli and it was active after solubilization, renaturation, and acidic treatment (El-Sohaimy et al, 2010 andMenzella, 2011). Optimal pH for the produced recombinant camel chymosin:…”
Section: Activity Measurement Of Recombinant Camel Chymosinmentioning
confidence: 99%
See 3 more Smart Citations